A novel monoclonal antibody of human stem cell factor inhibits umbilical cord blood stem cell ex vivo expansion - Fan Jie; Ding Xinxin; Jiang Yongping (Journal of Hematology & Oncology, 2012)
Abstract Stem cell factor (SCF) activates hematopoietic stem cell (HSC) self-renewal and is being used to stimulate the ex vivo expansion of HSCs. The mechanism by which SCF supports expansion of HSCs remains poorly understood. In cord blood ex vivo expansion assays, a newly produced anti-SCF monoclonal antibody (clone 23C8) was found to significantly inhibit the expansion of CD34+ cells. This antibody appears to bind directly to a part of SCF that is critical for biological activity toward expansion of CD34+ cells, which is located in the first 104 amino acids from the NH2-terminus.